The Fractionation of Factor V from Human Plasma - Giddings, John C. (Thrombosis and Haemostasis, 1974)
Human plasma from normal donors and from patients with polycythaemia vera was fractionated in order to obtain a preparation of highly purified factor V. Fresh plasma was initially treated with aluminium hydroxide to remove factors II, VII, IX and X. Fibrinogen, factor VIII and most of the immunoglobulins were removed by precipitation with ethanol at -5° C. Crude factor V was precipitated with dilute acetic acid at pH 5.1, and then further purified by precipitation with acridine lactate (Rivanol), extraction with sodium chloride solution and column chromatography on agarose gel. Factor V was purified four hundred times with specific activity of 2.5-6.0 units per mg. protein. The final concentrate was devoid of activity of other coagulation factors but was heterogeneous on disc Polyacrylamide gel electrophoresis and Immunoelectrophoresis against anti human serum. On rechromatography on agarose gel there was a single peak of factor V activity, the molecular weight of which was estimated to be 300,000.